Determinants of Banking Sector Profitability in Zimbabwe - Abel, Sanderson; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2016)
The study sought to establish the determinants of banking sector profitability in Zimbabwe during the period 2009-2014. The study specifically looked at the evolution and determinants of banking sector profitability after Zimbabwe adopted a multicurrency system. Employing the fixed effects panel regression models the study shows that banking sector profitability in Zimbabwe is driven by the quality of decisions made by bank management with regard to liquidity risk, credit risk, asset composition and management, expense management and capital size. The results implies that profitability of the Zimbabwean banking sector can be improved by increasing the quality of the assets, improving expense management, improving liquidity and capital levels. The study confirms that bank managers have a significant role in shaping the profitability of the sector. Keywords: Banking Profitability, External Determinants, Internal Determinants, Fixed Effects, Generalized Methods of Moments JEL Classifications: C23; G21; L25